(untitled) (The International Journal for Scientific Research, 2025)
The main objective of this study was to determine the impact of financial risks on indicators measuring the development of financial markets, focusing on the size of the financial market, given its importance in attracting and mobilizing capital, increasing liquidity, diversifying funding sources, managing risks, and supporting the development process. To achieve this objective, the study adopted an analytical methodology, collecting data from various sources, such as reports and statistical bulletins issued by the Capital Market Authority and the annual statistical reports issued by Tadawul (the Saudi Stock Exchange). This data was analyzed using appropriate statistical and analytical tools. The study employed simple linear regression and multiple linear regression to determine the impact of financial risks, measured by credit risk and market risk, on the size of the Saudi Stock Exchange, as measured by the market capitalization index and the number of listed companies. The study reached several conclusions, most notably: a statistically significant positive impact of credit risk on the market capitalization index and the number of companies listed on the Saudi Stock Exchange; a statistically significant positive impact of market risk on the market capitalization index and the number of listed companies; and a statistically significant positive impact of financial risk, measured by both credit and market risk, on the size of the Saudi Stock Exchange, as measured by the market capitalization index and the number of listed companies. Among the study’s key recommendations is the need for continuous development of risk management and hedging strategies in the Saudi Stock Exchange to mitigate financial risks.